Optimization and Cost Reduction of Pharmaceutical Inventory Management: A Case Study of a Government Hospital in Phitsanulok / การหาค่าเหมาะที่สุดและการลดต้นทุนในการบริหารคลังเวชภัณฑ์ยา: กรณีศึกษาโรงพยาบาลรัฐแห่งหนึ่งในจังหวัดพิษณุโลก - Liampreecha / สาลินี ชัยวีระไทย และวศิน เหลี่ยมปรีชา, Salinee Chaiveerathai and Wasin (Journal of Community Development Research (Humanities and Social Sciences); Vol 8 No 3 (2558): September - December 2015, 2015)
เวชภัณฑ์ยา เป็นองค์ประกอบที่สำคัญอย่างหนึ่งในการให้บริการแก่ประชาชน และมีผลกระทบอย่างมากต่องบประมาณการเงินที่ใช้ ในการดำเนินการของโรงพยาบาล การจัดซื้อจัดหาเวชภัณฑ์ยาให้มีความเพียงพอ และทันต่อความต้องการของผู้รับบริการจึงเป็นสิ่งที่ควรพิจารณาเป็นอันดับต้นๆ อย่างไรก็ตาม ถึงแม้มีเวชภัณฑ์ยาที่เพียงพอแล้ว แต่หากมีการจัดเก็บไว้คงคลังเป็นจำนวนมาก ย่อมก่อให้เกิดความสูญเสียงบประมาณ และเกิดต้นทุนจมโดยไม่จำเป็นได้ การศึกษาครั้งนี้ มุ่งเน้นการหาแนวทางในการจัดการเวชภัณฑ์ยาคงคลังให้มีประสิทธิภาพ โดยใช้วิธีวิเคราะห์แบบ ABC Analysis และ VEN System ร่วมกับการหาปริมาณการสั่งซื้อที่ประหยัด และการหาจุดสั่งซื้อใหม่ โดยพิจารณายาในกลุ่ม AN ซึ่งเป็นรายการยานอกบัญชียาหลักแห่งชาติที่มีมูลค่าการใช้สูง จากผลการศึกษา พบว่า วิธีการหาปริมาณการสั่งซื้อที่ประหยัด ทำให้ต้นทุนรวมในการจัดการยาคงคลังมากกว่าการใช้วิธีการดำเนินการในปัจจุบัน คิดเป็นร้อยละ 48.02   คำสำคัญ : การบริหารคลังเวชภัณฑ์ยา ปริมาณการสั่งซื้อที่ประหยัด จุดสั่งซื้อใหม่   Abstract Pharmaceutical inventory is one of the important factors in medical service. It is directly related to budget of the hospital management. Therefore, the sufficiency and efficiency of the pharmaceutical inventory management are the first priority to be considered. However, some hospitals choose to store too much medical supply. It leads to the ineffective budget management and unnecessary sunk cost. This study will focus on the optimization ofthe Pharmaceutical inventory using the ABC analysis and VEN system with Economic Order Quantity (EOQ) and Re-Order Point (ROP). Then, the AN group which is classified to non-essential drugs with highest usage value werechosen to be studied. The result of the study found that EOQ method is not more effective than the original method. Therefore, the total cost of theEOQ technique is more than the present method apploximately 48.02 percents.   Keywords: Pharmaceutical inventory management , Economic Order Quantity , Re-Order Point
Keywords: การบริหารคลังเวชภัณฑ์ยา ปริมาณการสั่งซื้อที่ประหยัด จุดสั่งซื้อใหม่ Pharmaceutical inventory management, Economic Order Quantity, Re-Order Point